Community policing in Danish "ghetto" areas: Trust and distrust between the police and ethnic minority youth. (February 2023) - Kammersgaard, Tobias; Søgaard, Thomas Friis; Haller, Mie Birk; Kolind, Torsten; Hunt, Geoffrey
Recent years have seen trends within police to use different forms of "community policing" strategies that aim to foster closer relationships and trust with citizens, as well as an orientation toward "procedural justice" in law enforcement practices. Based on 25 interviews with police officers in two different police precincts in Denmark, this article explores the policing of ethnic minority youth in so-called "ghetto" areas from the perspectives of police officers. In doing this, we describe the specific challenges and strategies in implementing such policing methods in neighborhoods where some residents display low trust or even hostility toward the police. The article sheds light on the emotional, organizational, and practical challenges involved in doing community policing in marginalized neighborhoods and the way in which this shapes how community policing is being organized in practice.